First-in-human phase I study of BPI-9016M, a dual MET/Axl inhibitor, in patients with non-small cell lung cancer - Hu, Xingsheng (J Hematol Oncol, 2020)
BACKGROUND: BPI-9016M is a novel small-molecule inhibitor that simultaneously targets both c-Met and AXL tyrosine kinases. This phase I study aimed to determine the maximum tolerated dose (MTD), safety, pharmacokinetics, and antitumor activity of BPI-9016M in Chinese patients with advanced non-small cell lung cancer (NSCLC). METHODS: Over the dose range of 100 mg to 800 mg, eligible patients were administered with a single dose of 9016M tablet and received 7 days of pharmacokinetics evaluation, followed by continuous dose administration (QD dosing, 28 days). Standard “3 + 3” dose escalations were performed. RESULTS: Twenty NSCLC patients were treated. All patients experienced at least one adverse event (AE), of which treatment-related adverse events (TRAEs) were reported in 17 (85.0%) patients. The most common TRAEs were alanine transaminase (ALT) elevation (60%), bilirubin increased (40%), dysgeusia (40%), constipation (30%), hypertension (25%), and palmar-plantar erythrodysesthesia syndrome (15%). The TRAEs of grade 3 or higher during treatment were hypertension (15%), pulmonary embolism (5%), and laryngeal pain (5%). No dose-limiting toxicity (DLT) was observed, and the MTD was not reached. The median time to C(max) ranged from 2.0 to 3.5 h, and the plasma concentration of BPI-9016M declined rapidly after T(max) fitting a single-compartment model. The mean AUC(0–72 h) of M1 and M2-2, main metabolites of BPI-9016M, were 4.8–6.6 folds and 4.1–9.8 folds higher than that of BPI-9016M, respectively. Exposure to BPI-9016M, M1, and M2-2 reached moderate saturation at 600 mg. Among 19 evaluable patients, 1 had a partial response and 10 patients had stable disease. CONCLUSION: BPI-9016M showed favorable safety and pharmacokinetic profiles, and no DLT was observed at doses up to 800 mg once daily. The promising antitumor activity in Chinese NSCLC patients supports further development of this tyrosine kinase inhibitor. TRIAL REGISTRATION: Clinical Trial ID: NCT02478866, registered May 21, 2015.